Effective recovery of rare earth from (bio)leaching solution through precipitation of rare earth-citrate complex. (15th April 2023) - Meng, Xiaoyu; Zhao, Hongbo; Zhao, Yu; Shen, Li; Gu, Guohua; Qiu, Guanzhou
Highlights: A new precipitation technology was proposed to recover RE-Cit complex. This new technology can efficiently recover rare earth with low impurity recovery. Pilot tests (1000 L) were successfully conducted. It is promising in rare earth (bio)hydrometallurgy and wastewater treatment. Abstract: Bioleaching is considered an alternative to traditional rare earth extraction technology. However, since rare earth elements exist as complexes in bioleaching lixivium, they cannot be directly precipitated by normal precipitants, which restricts their further development. This structurally stable complex is also a common challenge in various types of industrial wastewater treatment. In this work, a new method called a three-step precipitation process is first proposed to efficiently recover rare earth-citrate (RE-Cit) complexes from (bio)leaching lixivium. It consists of coordinate bond activation (carboxylation by pH adjustment), structure transformation (Ca 2+ addition) and carbonate precipitation (soluble CO3 2- addition). The optimization conditions are determined to adjust the lixivium pH to around 2.0, then add calcium carbonate until the n(Ca 2+ ): n(Cit 3- ) is more than 1.4:1 and lastly add sodium carbonate until n(CO3 2- ): n(RE 3+ ) is more than 4:1. The results of precipitation experiments using imitated lixivium show that the rare earth yield is more than 96% and the impurity aluminum yield is less than 20%. Subsequently, pilot tests (1000 L) using real lixivium were successfully conducted. The precipitation mechanism is briefly discussed and proposed by thermogravimetric analysis, Fourier infrared spectroscopy, Raman spectroscopy and UV spectroscopy. This technology is promising in the industrial application of rare earth (bio)hydrometallurgy and wastewater treatment due to its advantages of high efficiency, low cost, environmental friendliness and simple operation. Graphical abstract: Image, graphical abstract Schematic flowchart of the three-step precipitation route to recover RE-Cit complex from (bio)leaching lixivium and pilot test result.